Amphibole–melt disequilibrium in silicic melt of the Aso-4 caldera-forming eruption at Aso Volcano, SW Japan - Hidemi Ishibashi; Yukiko Suwa; Masaya Miyoshi; Atsushi Yasuda; Natsumi Hokanishi (Earth, Planets and Space, 2018)
Abstract The most recent and largest caldera-forming eruption occurred at ~ 90 ka at Aso Volcano, SW Japan, and is known as the “Aso-4 eruption.” We performed chemical analyses of amphibole phenocrysts from Aso-4 pyroclasts collected from the initial and largest pyroclastic unit (4I-1) of the eruption to infer the composition–temperature–pressure conditions of the melt that crystallized amphibole phenocrysts. Each amphibole phenocryst is largely chemically homogeneous, but inter-grain chemical variation is observed. Geothermometry, geobarometry, and melt–SiO2 relationships based on amphibole single-phase compositions reveal that most amphibole phenocrysts were in equilibrium with hydrous melt comprising ~ 63–69 wt% SiO2 ($${\text{SiO}}_{2}^{\text{melt}}$$ SiO2melt ) at 910–950 °C, although several grains were crystallized from more mafic and higher-temperature melts (~ 57–60.5 wt% SiO2 and 965–980 °C). The amphibole temperatures are comparable with those previously estimated from two-pyroxene geothermometry, but are much higher than temperatures previously estimated from Fe–Ti oxide geothermometry. The estimated $${\text{SiO}}_{2}^{\text{melt}}$$ SiO2melt contents are lower than that of the host melt in the 4I-1 pyroclasts. Chemical and thermal disequilibrium between the amphibole rims and the host melt, as well as intra-grain homogeneity and inter-grain heterogeneity of amphibole compositions, suggests that these amphiboles were incorporated into the host melt immediately prior to the caldera-forming eruption. Our results suggest that the amphibole phenocrysts, and perhaps some of the pyroxene and plagioclase phenocrysts, were derived from a chemically and thermally zoned crystal mush layer that had accumulated beneath the chamber of the host 4I-I melt. Amphibole geobarometry indicates a crystallization depth of ~ 13.9 ± 3.5 km, which is consistent with the present-day magma chamber depth beneath the volcano as inferred from geophysical observations. The results suggest that the depth of the post-caldera magma plumbing system is strongly influenced by a relic magma reservoir related to a previous caldera-forming eruption.